Resting Metabolic Rate in Indian Adolescents and Youth with Type 1 Diabetes Mellitus: A Case Controlled Study - Madhura Karguppikar; Shruti Mondkar; Nikhil Shah; Neha Kajale; Sarita Kulkarni; Ketan Gondhalekar; Shital Bhor; Vaman Khadilkar; Anuradha Khadilkar (Indian Journal of Endocrinology and Metabolism)
Introduction: Energy metabolism in type 1 diabetes (T1D) is known to be different. Resting metabolic rate (RMR) accounts for the largest portion of total energy needs. The objective of our study was to assess resting metabolic rate and its determinants in adolescents and young adults with T1D in comparison with age- and gender-matched healthy controls. Methods: This cross-sectional study included 97 children and young adults (10–19 years) with type 1 diabetes having a disease duration of at least 1 year. For the control population, 95 age- and gender-matched healthy adolescents were enrolled. Clinical examination and biochemical evaluation of parameters pertaining to diabetes and body composition were estimated, and RMR was measured using indirect calorimetry for both cases and controls. Results: Adolescents with T1D were significantly shorter, and had significantly lower calorie intake, higher RMR and volume of oxygen consumed (VO2) as compared to the healthy controls (P < 0.05). RMR adjusted for weight showed a significant positive correlation with lean body mass (LBM) percentage, and energy intake and a negative correlation with disease duration. Those with a T1D duration of less than 5 years demonstrated a significantly higher RMR, lower body fat percentage, higher LBM percentage, carbohydrate and energy intake/kg body weight and higher calculated insulin sensitivity (IS) as compared to those with greater disease duration. Muscle mass percentage and higher energy intake were found to be significant positive predictors and advancing age/diabetes duration was a negative predictor of weight-adjusted RMR (P < 0.05), whereas IS and male gender tended towards significant negative association (P = 0.06). Conclusion: Indian children with type 1 diabetes had a higher resting metabolic rate as compared to healthy children. Muscle mass, energy intake and diabetes duration were observed to be important predictors of RMR in T1D. Reduction in RMR with advancing age/disease duration may predispose to weight gain and subsequent double diabetes in T1D.